Walk or be walked by the dog? The attachment role - Catarina F. Martins; Luís Silva; Jorge Soares; Graça S. Pinto; Catarina Abrantes; Luís Cardoso; Maria A. Pires; Hélder Sousa; Maria P. Mota (BMC, 2024)
Abstract Background The human-animal bond has been recognized as having positive effects on the health and well-being of both humans and pets. The present study aims to explore the influence of attachment on physical activity (PA), lifestyle, and health outcomes of dog owners (DO), highlighting the mutual benefits resulting from the relationship between DO and dogs. Methods Thirty-eight DO and their dogs participated in this study. Socio-demographic data, the Self-Rated Health (SRH), FANTASTICO Lifestyle Scale, and the Lexington Attachment Pet Scale (LAPS) were assessed. PA was measured in both the DO and the dogs, using an ActiGraph GT3X accelerometer in the context of daily routine. Descriptive statistics and Spearman rank correlation analyses were performed to examine the associations between LAPS, PA levels, socio-demographic variables, lifestyle behaviors, and SRH. Results Significant correlations were found between the dog owners' light-level PA and the pets' vigorous level of PA (rho = 0.445, p = 0.01). Furthermore, the importance of the pets' health (rho = -0.785, p = 0.02) and the LAPS subscales, namely proximity (rho = 0.358, p = 0.03), and attachment (rho = 0.392, p = 0.01), were related to taking the pet for a walk. Regarding lifestyle, DO with a healthier lifestyle had a better self-assessment of their health using the SRH (rho = 0.39, p = 0.02). Moreover, DO with better lifestyles also exhibited greater concern for their pet's health (rho = 0.398, p = 0.01). Conclusions This study emphasizes that individuals who adopt healthier habits tend to perceive themselves as healthier and exhibit greater concern for their pets' health. The attachment between DO and dogs is important in promoting healthy lifestyle behaviors and engagement in PA. Our results highlight that the presence of a dog is associated with a higher level of PA in DO, depending on the strength of the human-animal bond.